Case Report: Adult degenerative scoliosis in two patients treated with percutaneous spinal endoscopic-assisted lumbar interbody fusion and percutaneous pedicle screw fixation - Du, Jian-wei; Zhang, Lei-ming; Yan, Yu-qiu; Zhang, Ya-ning; Rong, Xue-qin; Xiao, Song-hua; Zhang, Xi-feng (Frontiers in Surgery, 2023)
Adult degenerative scoliosis (ADS) is a serious disease that often affects middle-aged and elderly people. ADS does not only cause sagittal and coronal deformity of the lumbar spine, but it also causes severe back and leg pain secondary to the compression of the neural structures. Open surgery remains the main method for correcting the occurring deformity and decompression of the neural structures; however, its benefit is limited in cases of large trauma. Minimally invasive spinal (MIS) surgery is an alternative method that has recently witnessed rapid development. It has the advantage of providing rapid recovery with less trauma as compared to conventional open surgery. We report two cases of ADS treated with percutaneous spinal endoscopic-assisted lumbar interbody fusion (EALIF) and percutaneous pedicle screw fixation. Both cases had moderate deformities of the lumbar spine (load-sharing classification 4~7 points) with severe back and leg pain, and they underwent successful MIS surgery. At 6 months of follow-up, the visual analog scale (VAS), and Oswestry disability index (ODI) scores of both patients improved and the deformity was corrected. For moderate ADS, percutaneous spinal EALIF and percutaneous pedicle screw fixation may achieve an effective correction of the deformity with direct decompression of neural structures.